Rural peon's statute of Argentina: Brazilian's case compared with Argentinien's case - Barandiarán, Luciano Oscar (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2009)
In spite of the similarities mentioned by the regional historiography around the peronismo and to the varguismo like representatives of the populism, one of the most important differences between both regímens was its social politics for the field, especially toward the salaried rural workers. The sanction in 1944 of the Rural Peon's Statute in Argentina meant an important support to Perón during all its administration, while in Brazil, although Vargas impelled the first measures in favor of that same sector, the Rural Worker’s Statute newly was sanctioned in 1963. This work carries out an approach to those norms, considered by the historiography of both countries like the end of the exclusion of the rural workers of the law.